Clinically Mild Thrombasthenia with Normal Platelet Coagulant Activities - Walsh, P. N; Rizza, C. R; McLennan, R (Thrombosis and Haemostasis, 1972)
The results of assaying platelet coagulant activities in a patient with clinically mild thrombasthenia are compared with those previously reported in 4 patients with clinically severe and 2 patients with moderately severe thrombasthenia. Contact product forming activity and platelet factor 3 activity were normal in the present patient, and decreased in the more severely affected patients. Intrinsic factor-Xa forming activity was normal or supranormal in all patients. Collagen-induced coagulant activity was present in mildly and moderately affected patients and absent in severely affected patients. The present patient would appear to possess both alternative mechanisms by which platelets can initiate intrinsic clotting, compared to the moderately affected patients who lack one and the severely affected patients who lack both pathways. Although the present patient’s platelets failed to aggregate in response to ADP they responded normally to ADP in the assay for contact product forming activity.